MicroRNA-Mediated Regulation of ITGB3 and CHL1 Is Implicated in SSRI Action - Oved, Keren; Farberov, Luba; Gilam, Avial; Israel, Ifat; Haguel, Danielle; Gurwitz, David; Shomron, Noam (Frontiers in Molecular Neuroscience, 2017)
Background: Selective serotonin reuptake inhibitor (SSRI) antidepressant drugs are the first-line of treatment for major depressive disorder (MDD) but are effective in <70% of patients. Our earlier genome-wide studies indicated that two genes encoding for cell adhesion proteins, close homologue of L1 (CHL1) and integrin beta-3 (ITGB3), and microRNAs, miR-151a-3p and miR-221/222, are implicated in the variable sensitivity and response of human lymphoblastoid cell lines (LCL) from unrelated individuals to SSRI drugs. Methods: The microRNAs miR-221, miR-222, and miR-151-a-3p, along with their target gene binding sites, were explored in-silico using miRBase, TargetScan, microRNAviewer, and the UCSC Genome Browser. Luciferase reporter assays were conducted for demonstrating the direct functional regulation of ITGB3 and CHL1 expression by miR-221/222 and miR-151a-3p, respectively. A human LCL exhibiting low sensitivity to paroxetine was utilized for studying the phenotypic effect of CHL1 regulation by miR-151a-3p on SSRI response. Results: By showing direct regulation of CHL1 and ITGB3 by miR-151a-3p and miR-221/222, respectively, we link these microRNAs and genes with cellular SSRI sensitivity phenotypes. We report that miR-151a-3p increases cell sensitivity to paroxetine via down-regulating CHL1 expression. Conclusions: miR-151a-3p, miR-221/222 and their (here confirmed) respective target-genes, CHL1 and ITGB3, are implicated in SSRI responsiveness, and possibly in the clinical response to antidepressant drugs.